Selective Targeting of a Disease-Related Conformational Isoform of Macrophage Migration Inhibitory Factor Ameliorates Inflammatory Conditions - Thiele, Michael; Kerschbaumer, Randolf J; Tam, Frederick W K; Völkel, Dirk; Douillard, Patrice; Schinagl, Alexander; Kühnel, Harald; Smith, Jennifer; McDaid, John P; Bhangal, Gurjeet; Yu, Mei-Ching; Pusey, Charles D; et al. (The Journal of immunology (1950), 2015)
Macrophage migration inhibitory factor (MIF), a proinflammatory cytokine and counterregulator of glucocorticoids, is a potential therapeutic target. MIF is markedly different from other cytokines because it is constitutively expressed, stored in the cytoplasm, and present in the circulation of healthy subjects. Thus, the concept of targeting MIF for therapeutic intervention is challenging because of the need to neutralize a ubiquitous protein. In this article, we report that MIF occurs in two redox-dependent conformational isoforms. We show that one of the two isoforms of MIF, that is, oxidized MIF (oxMIF), is specifically recognized by three mAbs directed against MIF. Surprisingly, oxMIF is selectively expressed in the plasma and on the cell surface of immune cells of patients with different inflammatory diseases. In patients with acute infections or chronic inflammation, oxMIF expression correlated with inflammatory flare-ups. In addition, anti-oxMIF mAbs alleviated disease severity in mouse models of acute and chronic enterocolitis and improved, in synergy with glucocorticoids, renal function in a rat model of crescentic glomerulonephritis. We conclude that oxMIF represents the disease-related isoform of MIF; oxMIF is therefore a new diagnostic marker for inflammation and a relevant target for anti-inflammatory therapy.